2020
DOI: 10.1126/sciadv.aba4294
|View full text |Cite
|
Sign up to set email alerts
|

Self-powered user-interactive electronic skin for programmable touch operation platform

Abstract: User-interactive electronic skin is capable of spatially mapping touch via electric readout and providing visual output as a human-readable response. However, the high power consumption, complex structure, and high cost of user-interactive electronic skin are notable obstacles for practical application. Here, we report a self-powered, user-interactive electronic skin (SUE-skin), which is simple in structure and low in cost, based on a proposed triboelectric-optical model. The SUE-skin achieves the conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(76 citation statements)
references
References 39 publications
0
70
0
Order By: Relevance
“…From the traditional keyboards ( Ahmed et al., 2017 ; Chen et al., 2015 ; Jeon et al., 2018 ; Wang et al., 2018a ; Wu et al., 2018a ; Yang et al., 2013 ) and touch pads ( Chen et al., 2018 ; Dong et al., 2018 ; Shi et al., 2019a ) to the rising electronic skin ( Chang et al., 2020 ; Lai et al., 2016 , 2019 ; Wu et al., 2017 ), the tactile sensors are developed to be more flexible, sensitive, efficient, and multi-functional, even with human-like intelligence. In this part, six examples of TENG-based tactile sensors are reviewed: a high-resolution pressure-sensitive TS matrix for tactile mapping ( Wang et al., 2016 ); an elastic metal-free tactile sensor for detecting both normal and tangential forces ( Ren et al., 2018 ); a transparent and attachable ionic hydrogel-based pressure sensor for coded communication ( Lee et al., 2018 ); a flexible touch pad with subdivided units for tactile XY positioning ( Pu et al., 2020 ); a user-interactive electronic skin for touch track mapping based on the triboelectric-optical model ( Zhao et al., 2020 ); and a triboelectric tactile sensor producing various amplitudes of signals based on the history of pressure stimulations for mimicking neuromorphic functions of synaptic potentiation and memory ( Wu et al., 2020 ).…”
Section: Biomedical Monitoring Integrated Hmismentioning
confidence: 99%
See 2 more Smart Citations
“…From the traditional keyboards ( Ahmed et al., 2017 ; Chen et al., 2015 ; Jeon et al., 2018 ; Wang et al., 2018a ; Wu et al., 2018a ; Yang et al., 2013 ) and touch pads ( Chen et al., 2018 ; Dong et al., 2018 ; Shi et al., 2019a ) to the rising electronic skin ( Chang et al., 2020 ; Lai et al., 2016 , 2019 ; Wu et al., 2017 ), the tactile sensors are developed to be more flexible, sensitive, efficient, and multi-functional, even with human-like intelligence. In this part, six examples of TENG-based tactile sensors are reviewed: a high-resolution pressure-sensitive TS matrix for tactile mapping ( Wang et al., 2016 ); an elastic metal-free tactile sensor for detecting both normal and tangential forces ( Ren et al., 2018 ); a transparent and attachable ionic hydrogel-based pressure sensor for coded communication ( Lee et al., 2018 ); a flexible touch pad with subdivided units for tactile XY positioning ( Pu et al., 2020 ); a user-interactive electronic skin for touch track mapping based on the triboelectric-optical model ( Zhao et al., 2020 ); and a triboelectric tactile sensor producing various amplitudes of signals based on the history of pressure stimulations for mimicking neuromorphic functions of synaptic potentiation and memory ( Wu et al., 2020 ).…”
Section: Biomedical Monitoring Integrated Hmismentioning
confidence: 99%
“… (E) User-interactive electronic skin for touch track mapping based on the triboelectric-optical model. Reproduced with permission, from ref ( Zhao et al., 2020 ), Copyright 2020, American Association for the Advancement of Science. (F) Triboelectric tactile sensor producing various amplitudes of signals based on the history of pressure stimulations for mimicking neuromorphic functions of synaptic potentiation and memory.…”
Section: Biomedical Monitoring Integrated Hmismentioning
confidence: 99%
See 1 more Smart Citation
“…These peaks contain valuable cardiovascular information regarding the subject's health, which can be decoded from the sensory output of the proposed TENG device. Recently, Zhao et al reported a self-powered and user-interactive electronic skin (SUE-skin) with a triboelectric-optical model, exhibiting a new application of the wearable TENGs for touch operation platform (Zhao et al, 2020). The SUE-skin that can generate electrical and optical signals simultaneously under touch stimuli is shown in Figure 2C.…”
Section: Wearable Triboelectric Nanogeneratorsmentioning
confidence: 99%
“…With the development of materials science, sensors with flexible substrates have gradually attracted people’s attention, especially the enthusiasm for research on electronic skin is increasing. Due to the flexibility, high sensitivity, high fit, and comfort of electronic skin [ 1 , 2 , 3 , 4 ], it can sense different external pressure like human skin as a biomedical sensor, that is, it has smooth conductive tactile signals. Flexible sensors can be applied not only to the medical field, but also to wearable devices and intelligent robot systems [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%